POLITISASI PENDIDIKAN AGAMA BAGI KETURUNAN SEDULUR SIKEP DALAM RUANG LEMBAGA FORMAL DI KUDUS - Fitriyah, Anis (Pascasarjana IAIN Kudus, 2015)
The existence of students from Sedulur Sikep generation in formal institutions is in a positive situation, because historically Sedulur Sikep as a community is not educated people, however, on the other hand their existence raises new polemic related to religious education they may take due to the political issues about the religious education at formal education institutions includes six religions, namely Islamic religious education, Christian religious education, Chatholic religious education, Hindu religious education, Buddhist religious education, and education of Confucianism. While students from Sedulur Sikep generation recognize other religion exclude those six religions. Here, the formal institutions in Kudus use and interpret religious education differently from the purpose and function of religious education, for the fulfillment of general education for students from Sedulur Sikep generation in the space of formal institutions in Kudus.keberadaan siswa keturunan Sedulur Sikep di lembaga formal, pada satu sisi merupakan keadaan yang positif,karena secara historis Sedulur Sikep dianggap sebagai komunitas yang tidak berpendidikan dalam artian (tidak bersekolah formal-red), namun pada sisi yang lainnya keberadaan siswa keturunan Sedulur Sikep memunculkan polemik baru terkait pendidikan agama yang harus mereka jalani. Karena permasalahan politis yang menyatakan pendidikan agama pada lembaga formal mencakup enam agama yaitu Pendidikan agama Islam, Pendidikan agama Kristen, Pendidikan agama katolik, Pendidikan agama hindu, Pendidikan agama buddha, dan Pendidikan agama konghucu. Sementara siswa keturunan Sedulur Sikep mengakui agama secara berbeda dari ke enam agama tersebut. Sehingga di sini pihak lembaga formal di kudus menggunakan serta menafsirkan pendidikan agama secara berbeda dari tujuan dan fungsi pendidikan agama, demi terpenuhinya pendidikan secara umum bagi siswa keturunan Sedulur Sikep dalam ruang lembaga formal di kudus